(untitled) (Research, Society and Development, 2025)
Objective: To analyze and correlate the impact of human lifestyle habits on pulmonary diseases, considering the interaction between the respiratory and intestinal systems, in order to clarify the positive or negative determinants in the prognosis of lung diseases by investigating the immunological mechanisms of this interconnection, as well as the factors that contribute to patient quality of life and treatment. Methodology: This is an integrative literature review, with searches conducted in LILACS (Latin American and Caribbean Literature in Health Sciences), Scientific Electronic Library Online (SciELO), UNESP Institutional Repository, UFJF Institutional Repository, and PubMed (National Library of Medicine), using the descriptors “Microbiota,” “Lung,” “Gut,” and “Lung-gut axis.” Results: A total of 16 articles published between 2017 and 2024 in Portuguese and English were analyzed. The findings showed that intestinal dysbiosis, influenced by diet and obesity, is associated with chronic inflammation and oxidative stress, contributing to the progression of conditions such as asthma and lung cancer. Therapeutic strategies including probiotics, prebiotics, dietary interventions, and fecal microbiota transplantation demonstrated potential in modulating the lung-gut axis. Conclusion: The functional interaction between the intestinal and respiratory systems proves to be key to understanding respiratory syndromes and paves the way for personalized therapeutic approaches. However, further clinical trials and standardized protocols are required for more effective implementation.